Clipping or extracting: two ways to membrane protein degradation - Avci, Dönem; Lemberg, Marius (Trends in cell biology, 2015)
Protein degradation is a fundamentally important process that allows cells to recognize and remove damaged protein species and to regulate protein abundance according to functional need. A fundamental challenge is to understand how membrane proteins are recognized and removed from cellular organelles. While most of our understanding of this mechanism comes from studies on p97/Cdc48-mediated protein dislocation along the endoplasmic reticulum (ER)-associated degradation (ERAD) pathway, recent studies have revealed intramembrane proteolysis to be an additional mechanism that can extract transmembrane segments. Here, we review these two principles in membrane protein degradation and discuss how intramembrane proteolysis, which introduces an irreversible step in protein dislocation, is used to drive regulated protein turnover.